Analisis Penerapan Supplied By Owner Material Konstruksi Beton Terhadap Biaya Dan Tingkat Komponen Dalam Negeri (TKDN) Pekerjaan Konstruksi Jaringan Irigasi Ciwates: Analysis Of The Implementation Of Supplied By Owner Concrete Construction Materials On Cost And Domestic Component Level (TKDN): Ciwates Irrigation Network Construction Works - Aditya Wibawa Mukti; Bambang Priyambodo; Pio Ranap Tua Naibaho (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Amidst global food security challenges and post-pandemic economic fluctuations, the development of robust agricultural infrastructure has become an inevitable national priority, as outlined in Presidential Instruction Number 2 of 2025. However, fiscal realities at the regional level often present a paradox: the need for infrastructure rehabilitation is increasing while fiscal space is narrowing. This research highlights this phenomenon in Serang Regency, where the budget trend for irrigation management shows a significant decline from 2021 to 2025. This thesis proposes and tests the effectiveness of the Supplied by Owner (SBO) procurement method as a technocratic solution to bridge this gap. Through a case study approach on the Ciwates Irrigation Network Improvement project, this research conducts an in-depth comparative analysis of two key variables: construction cost efficiency and the optimization of Domestic Component Level (TKDN) in concrete works. The methodology combines contract document analysis, market price simulation, and material supply chain audit. The research results reveal empirical findings that the implementation of SBO is capable of generating a cost efficiency of 3.04% (equivalent to IDR 57,380,000.00) from a total conventional project value of IDR 1,886,459,000.00 to IDR 1,829,079,000.00. More significantly, this method proved to be a strong catalyst for increasing TKDN through the use of PT. Conch Cement Indonesia products, recording an increase of 9.21 percentage points from 52.18% to 61.39%. These findings confirm that SBO is not merely a savings mechanism, but a strategic instrument for quality control and the affirmation of national industrial policy. This study recommends the institutionalization of SBO in regional procurement regulations for material-intensive projects.